APLIKASI KOMPOS BATANG PISANG TERHADAP PERTUMBUHAN SEMAI JABON (Anthocephalus cadambaMiq.) PADA MEDIUM GAMBUT - Charlita Herantoro Pribadi; M. Mardhiansyah '; Evi Sribudiani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Banana are plant that bear fruit only once in its life cycle. Farmer usually replace with a new banana plant to maximize land or planting cycle, without managing to take advantage of the waste. Peat soil is a slow process of decomposition, has a low pH (acid), the poor in a number of nutrient both macro and micro, so that the plant growth is inhibited by using the peat medium, it is necessary to look for an alternative method in order to get a good seedling medium. This study aimed to determine the best dosage for seedling growth Jabon (Anthocephalus cadamba Miq.). This study used a completely randomized design (CRD), consisting of 4 treatments and 10 replications. T0= without giving compost banana trunk; T1=125g/polybag; T2=250g/polybag; T3=375g/polybag. The result showed that administration of a dose of compost banana trunk 375g/polybag on peat medium was the best treatment in the observation parameters, height gain (4.80 cm), the increase in diameter (3.21 mm), seedling dry weight (23.25 g), the ratio ofthe root crown (2.44 g). Keywords: compost, banana trunk, Anthocephalus cadamba Miq., peat medium